A study from the perspective of millennials: What influence housing purchase decision? / Nur Atasha Alina Kamarulzaman and Nur Anis Nafisah Zahari - Kamarulzaman, Nur Atasha Alina; Zahari, Nur Anis Nafisah (2022)
This study was also conducted for millennials aged between 20 – 40 years old who live and work in Selangor. This study was carried within two semesters, which starts from October 2022 until August 2022. The purpose of the study was to know the readiness in housing purchase decision among millennials and to know the relationship between independent variable and dependent variable, and to know determine the difference between housing purchase decision based on demographic factors (age and income). This study employed multi stage sampling in collecting the survey data. The result of the study revealed three important findings. First, majority of the respondents have the readiness in housing purchase decision. Secondly, there is significant relationship between housing location, financial capability, housing attributes, housing neighbourhood and housing knowledge towards housing purchase decision. Lastly, there is significant difference between housing purchase decision based on the demographic factor (age and income). The majority respondents which 348 out of 390 respondents (89.0%) have the readiness to make housing purchase decision. Independent variables significantly influenced the housing purchase decision among millennials with the correlation between the determinant factors; the housing location, financial capability, housing attributes, housing neighbourhood and housing knowledge are (r = 0.900), (r = 0.698), (r = 0.545), (r = 0.499), and (r = 0.605). There is a significant difference between housing purchase decision based on demographic factors (age and income) where age, F (6,383) =3.929, p=0.001, p<0.05 and income, F (5,384) =7.925, p=0.000, p<0.05. Based on the discussion on the findings, this study proposed several recommendations which are improve financial literacy, equip people in housing knowledge and build more affordable house at strategic location.